Izbor optimalnog visinskog sustava na primjeru budućeg nivelmana Bosne i Hercegovine : Selection of the optimal heights system on the example of Bosnia and Herzegovina's future leveling network - Asim Bilajbegović (Geodetski Glasnik, 2013)
U radu su obavljena istraživanja o izboru najpovoljnijeg sustava visina za buduće državne nivelmanske mreže, na primjeru Bosne i Hercegovine. Istraživanja imaju općeniti karakter i mogu se implementirati i za nivelmane visoke točnosti drugih država, posebno onih iz regiona. : Research on the best appropriete heights system to be selected for the future state leveling networks on the example of Bosnia and Herzegovina is shown. Research has the general approach and could be applied for High Precision Leveling Networks for the other countries and especially those from the region.